Mouse Models of Influenza Infection with Circulating Strains to Test Seasonal Vaccine Efficacy - Groves, Helen T.; McDonald, Jacqueline U.; Langat, Pinky; Kinnear, Ekaterina; Kellam, Paul; McCauley, John; Ellis, Joanna; Thompson, Catherine; Elderfield, Ruth; Parker, Lauren; Barclay, Wendy; Tregoning, John S. (Frontiers in Immunology, 2018)
Influenza virus infection is a significant cause of morbidity and mortality worldwide. The surface antigens of influenza virus change over time blunting both naturally acquired and vaccine induced adaptive immune protection. Viral antigenic drift is a major contributing factor to both the spread and disease burden of influenza. The aim of this study was to develop better infection models using clinically relevant, influenza strains to test vaccine induced protection. CB6F1 mice were infected with a range of influenza viruses and disease, inflammation, cell influx and viral load were characterised after infection. Infection with circulating H1N1 and representative influenza B viruses induced a dose dependent disease response; however a recent seasonal H3N2 virus did not cause any disease in mice, even at high titres. Viral infection led to recoverable virus, detectable both by plaque assay and RNA quantification after infection, and increased upper airway inflammation on day 7 after infection comprised largely of CD8 T cells. Having established seasonal infection models, mice were immunised with seasonal inactivated vaccine and responses were compared to matched and mismatched challenge strains. Whilst the H1N1 subtype strain recommended for vaccine use has remained constant in the seven seasons between 2010 and 2016, the circulating strain of H1N1 influenza (2009 pandemic subtype) has drifted both genetically and antigenically since 2009. To investigate the effect of this observed drift on vaccine induced protection, mice were immunised with antigens from A/California/7/2009 (H1N1) and challenged with H1N1 subtype viruses recovered from 2009, 2010 or 2015. Vaccination with A/California/7/2009 antigens protected against infection with either the 2009 or 2010 strains, but was less effective against the 2015 strain. This observed reduction in protection suggests that mouse models of influenza virus vaccination and infection can be used as an additional tool to predict vaccine efficacy against drift strains.